Effects of mastery learning and individualised strategies on students’ learning outcome in social studies in Lagos State (2019)
The study investigated the effects of mastery learning and individualised instructional strategies on students' achievement in Social Studies in Lagos State. The study adopted pre-test – post-test control group in a quasi-experimental design, while a multi-stage sampling technique was employed to select a sample of 150 students for the study. Four validated instruments, namely: Mastery learning and Individualised-instructional Strategy Questionnaire (r = 0.74); Socio-economic Background Questionnaire (r = 0.86); Students' Self-Efficacy Questionnaire (r = 0.64) and Social Studies Achievement Test (r = 076) were used to gather information in this study. Data obtained were analysed using Analysis of Covariance (ANCOVA) at 0.05 level of significance. The main effect of treatment was significant on students' achievement in social studies (F (3, 1231) = 8.971; P < 0.05). The interaction effect of treatment and socio- economic background was significant on students' achievement in social studies (F (4,123) = 5.794; P < 0.05). The second-order interaction effect of treatment, socio-economic background and self-efficacy was significant on students' achievement in social studies (F (2,123) = 6.360; P < 0.05). The results indicated a significant main effect of treatment on students' achievement in Social Studies. The study thus recommends that social studies teachers should be encouraged to employ mastery learning teaching strategy in the teaching-learning process in order to enhance desirable learning outcomes while students should be motivated to develop self-efficacy as this would help them become efficient in their studies.